Pembentukan Kelompok Teman Sebaya dan Pengenalan Rapid Test Napza Beserta Yoga Healing di SMP Tawwakal Denpasar Bali - Anak Agung Gde Oka Widana; Ni Wayan Desi Bintari; Diah Prihatiningsih; Ika Setya Purwanti; Ni Luh Putu Devhy (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service activity aims to form a peer group and introduce the Rapid Test for Drugs and Yoga Healing for Tawwakal Junior High School students, Denpasar Bali. The method of activities carried out is by way of guidance and counseling. The participants of this community service were 24 students, with evaluation instruments used in the form of pre and post test questionnaires. The results of this community service show that; (1) The introduction of Yoga Healing at SMP Tawakkal Denpasar can be implemented through basic breathing processing exercises to control stress, (2) The formation of peer groups is carried out well through the concept of groups organized based on the calculation of the gender characteristics of the participants, and (3 ) The results of the Pre Test and Post Test questionnaires showed a significant increase in student understanding at Tawakkal Junior High School Denpasar regarding the mechanism of drug testing and the dangers of drug abuse.